Successful surgical treatment of supradiaphragmatic descending thoracic aorta coarctation with anomalous origin of truncus coeliacus - D. O. Dzyurman; M. P. Radchenko; E. O. Artemenko; B. B. Serdenko; N. M. Rudenko; I. M. Yemets (Ukrainian Journal of Cardiovascular Surgery, 2018)
Middle aortic syndrome (MAS) is a segmental narrowing of the abdominal or distal descending thoracic aorta that is produced by congenital or by a number of acquired etiologies. MAS may be caused by Takayasu’s or temporal arteritis (giant cell arteritides), neurofibromatosis, fibromuscular dysplasia, retroperitoneal fibrosis, mucopolysaccharidosis, and Williams syndrome, or congenital, ascribed to a developmental anomaly in the fusion and maturation of the paired embryonic dorsal aortas.Aim of this article is to present a clinical case of successful surgical treatment of middle aortic syndrome with anomalous truncus coeliacus (supradiaphragmatic origin and above coarctation segment) in 3-year-old patient. Material and methods. In this article we offer the case of a 3-year-old female patient with middle aortic syndrome (supradiaphragmatic coarctation of descending thoracic aorta) and anomalous truncus coeliacus. The final diagnosis was established with computed tomography. Computed tomography revealed quite unusual origin of truncus coeliacus (its origin was supradiaphragmatic and above coarctation). She has undergone a successful surgical treatment, end-to-end extended anastomosis technique with truncus coeliacus reimplantation.Results. Four months follow-up CT imaging showed no distortions and no restenosis at the anastomosis site. At 4 month follow-up examination patient was asymptomatic with no neurological dysfunction.Conclussion. End-toend extended anastomosisis is relatively safe technique and an effective method of treatment for atypical coarctation with significant postoperative reduction of arterial blood pressure.